STRATEGI MENANAMKAN KECERDASAN MULTIKULTURAL PADA ANAK USIA DINI DI PAUD GRIYA NANDA - Nurhaliza, Nurhaliza; Yusuf, Yusri Az-zahro; Ma’rifah, Indriyani (Universitas Negeri Malang, 2023)
Instilling the value of multiculturalism in early childhood is very important. This study aims to determine the strategies used in building multicultural intelligence in early childhood at Griya Nanda PAUD. This research is a field study research and seen from the type of data, this research is a qualitative research. The data collection techniques used are interviews, observation, and documentation. The results showed that PAUD Griya Nanda implemented an effective strategy in building multicultural intelligence in early childhood. The teacher uses various methods such as national anthems, folk songs, audio-visual performances, and traditional dances from various regions. In addition, activities such as parades in traditional clothes on Kartini Day and August 17 are also carried out to increase understanding of cultural diversity. An inclusive and friendly learning environment is also provided to make it easier for children to interact with friends who have various backgrounds. Thus, children can get used to and be trained in accepting cultural differences, so as to increase multicultural intelligence in early childhood.